Need and acceptability of story books intended to help with the process of informing children about their HIV status in Malawi: a mixed methods study - Kalembo, F.; Kendall, Garth; Ali, Mohammed; Chimwaza, A. (Routledge, 2018)
The rate of disclosure of HIV status to children living with HIV in sub-Saharan Africa remains low despite the World Health Organisation’s recommendation that children should be told about their HIV status by the age of 12 years. Authors of previous studies have identified lack of disclosure materials as the main barrier to disclosure of HIV status. This study aimed to assess the need and acceptability of a series of age-appropriate children story books intended to help with informing children about their HIV status. Questionnaires, interviews, and focus group discussions were used to collect data from caregivers, healthcare workers, and school teachers, adolescents living with HIV, and community leaders across the three administrative regions of Malawi. Information about the need and acceptability of the story books and the sociodemographic characteristics of the participants was collected using reliable instruments. Quantitative data were tabulated while thematic analysis was used to analyse qualitative data. Almost 600 participants responded to the survey questionnaire, and 19 interviews and 12 focus groups were conducted with 106 participants. Ninety-eight per cent of participants supported the idea of developing the proposed series of story books and reported that they would use the books once they are developed. Most of the participants expressed that the books will help to improve their knowledge and understanding of HIV disclosure, increase their confidence on how to disclose and help to provide consistent information about HIV disclosure to children.The results of this study show a high acceptability rate of the story books. The process of HIV disclosure to children is a very complex issue that will require the development of guidelines and materials that are rigorously evaluated prior to dissemination.